Design and fabrication two degree of freedom free vibration translation motion test rig - Muhammad Maghribi, Selamat (2013)
This project is about the designing and fabrication the two degree of freedom freevibration translation motion test rig. The objective of this project is to design and fabricate the two degree of freedom free vibration translation motion test rig. Thestudy on the free vibration system of two degree of freedom is very important. This theory need to be carried out by doing experimental study. This test rig will bedeveloped based on the vibration fundamental knowledge. The fabrication processstarts with understanding the fundamental of mechanical vibration. Sketching and design process will be developed in multiple choices in order to select the best designconcept of the test rig. Material selection and the factor of the selection also havebeen listed based on the appropriate criteria predetermined. The selection material will undergo several fabrication process based on the chose design. Finally the test rigwill be tested in the vibration laboratory.